Identification of Mab-binding epitopes on foot-and-mouth disease virus serotype Asia 1 represented in anti-FMDV Asia 1 polyclonal sera - SANYAL, A; VENKATARAMANAN, R; PATTNAIK, B; HEMADRI, D; TOSH, C (The Indian Journal of Animal Sciences, 2014)
A panel of 17 neutralizing monoclonal antibodies (Mabs) was used to assess their competing ability with polyclonal antibodies to sce the relevancc or the Mab-binding cpitopes in polyclonal sera. Variable degree of binding inhibition of the Mabs of 146s particle in the presence of poiyclonal antibodies was observed and based on the per cent compctition/ inhibition the MabH could be clustered into 4 different groups. The Mabs generated in mice recognized the antigenic site(s) detected by neutralizing antibodies that developed in the experimental/ natural host species following infection/ vaccination and guinca-pig serum contains antibodies against more number of Mab-binding sites compared to bovine vaccinatc serum. Thc sites represented by the Mabs of group 1 lire immunodominant and have sufficient polyelonal countcrpnrtH i.c. the binding sites recognized by these Mabs arc well represcnted in both the sera and could be important in terms of protection in animals.